Flexible response and rapid recovery strategies of the plateau forage Poa crymophila to cold and drought - Li, Xin-Yu; Wang, Yan; Hou, Xin-Yi; Chen, Yan; Li, Cai-Xia; Ma, Xin-Rong (Frontiers in Plant Science, 2022)
Cold and drought stresses are the two severely abiotic stresses in alpine regions. Poa crymophila is widely grown in Qinghai Tibet Plateau with the strong tolerance. Here, by profiling genes expression pattern and metabolomics-associated transcriptomics co-expression network, the acclimation of Poa crymophila to the two stresses was characterized. (1) The genes and metabolites with stress tolerance were induced by cold and drought, while those related growth were inhibited, and most of them could restore fast after stresses disappeared. Especially, the photosynthesis system genes had strong resilience. (2) Additionally, cold and drought activated hypoxia and UV-B adaptation genes, indicating long-term life on the plateau could produce special adaptations. (3) Phenolamines, polyamines and amino acids, especially N',N'',N'''-p -coumaroyl-cinnamoyl-caffeoyl spermidine, putrescine and arginine, exerted key roles in harsh environment. The flexible response and quick recovery are strategies for adaptation to drought and cold in P. crymophila, accounting for its robust tolerance and resilience. This paper presented a comprehensive stress response profile of P. crymophila, and provided many candidate genes or metabolites for future forage improvement.